AWARENESS AND PRACTICES ABOUT BIO-MEDICAL WASTE AMONG HEALTH CARE WORKERS IN TERTIARY CARE HOSPITAL OF HALDWANI, NAINITAL - Mukesh Kumar; Rajesh Kumar Singh; Umesh; Vinita Rawat (National Journal of Medical Research, 2015)
Background: The biomedical waste poses significant hazardous risk to the patients, healthcare workers, the community and environments. Thus the knowledge regarding biomedical waste management among health care personnel have greater impact on health and environment. This study aims to assess the awareness and practices regarding biomedical waste management among Health care workers in Tertiary care hospital.